Identification of patterns in the structural and phase composition of the doping alloy derived from metallurgical waste processing - Poliakov, Anatolii; Dzyuba, Anatolii; Volokh, Vadym; Petryshchev, Artem; Tsymbal, Bohdan; Yamshinskij, Mykhail; Lukianenko, Ivan; Andreev, Andrey; Bilko, Tamara; Rebenko, Victor (Eastern-European Journal of Enterprise Technologies, 2021)
This paper reports a study into the structural-phase composition of the doping alloy made by processing metallurgical anthropogenic waste involving reduction smelting. This is required for determining the technological parameters that ensure an increase in the level of extraction of target elements during the processing of anthropogenic waste and for the further use of the doping alloy. It was revealed that the phase composition of the doping alloy manifested a solid solution of the doping elements and carbon in α-Fe. Cementite Fe3C and silicides Fe5Si3, FeSi, and FeSi2 were also identified. In this case, the doping elements were more likely to act as substitution atoms. It has been determined that the microstructure of the alloy consisted of several phases of different shapes and contents of the basic doping elements. Sites with an elevated iron level of up to 95.87 % by weight in the composition could be represented by the solid solution phase of the doping elements and carbon in α-Fe. The sites with a relatively high (% by weight) content of carbon (0.83‒2.17) and doping elements ‒ W, up to 39.41; Mo, up to 26.17; V, to 31.42; Cr, to 9.15 ‒ were apparently of a carbide nature. The sites with a silicon content of 0.43‒0.76 % by weight likely included silicide compounds. The alloy’s characteristics make it possible to smelt steel grades without strict carbon restrictions, replacing some of the standard ferroalloys. Neither phases nor compounds with a relatively high propensity for sublimation were identified in the material produced. Therefore, there is no need to provide conditions to prevent evaporation and loss in the gas phase of the doping elements. That could increase the degree of extraction of the doping elements